If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4v + 6v = -16 Combine like terms: -4v + 6v = 2v 2v = -16 Solving 2v = -16 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Divide each side by '2'. v = -8 Simplifying v = -8
| 4x^4+2x^3-39x^2+43x-10=0 | | 6x-8x+10=87-21+10x | | x-(-11)=18 | | -7(2t+3)=-35 | | s*4-46=-2 | | 49x+1.5=25x+3 | | 3x-7-4x+11=6x-3 | | 12a+12a+7a+7a= | | 40c+8=48c-20 | | -30=-5+5 | | 3x-7-4x+11=6x-7 | | 2f=10 | | 10+5(a-3)=9-2a | | tg(2x)=0.6 | | 2z^2-15z+7=0 | | 7(x-6)=56 | | x^2-10x+6=1 | | 7(3s+4)=133 | | 3z+3z+4z+3+4z+3=132 | | 3f=9 | | 8(2l+8)=112 | | 3x+1+1x+11=180 | | 5*(5*(5*(5+4)+3)+2)+1= | | x+13=111 | | 6k+k-3k+3=19 | | 7h+18=214 | | -2(x+7)=14 | | 2A+2b=bc | | f(2n+1)=f(n)+f(n-1) | | 6x-6=-15 | | (q-9)*4=8 | | (9c+5)(7c-1)=0 |